RANCANG BANGUN FIXTURE DALAM PROSES PENGENDURAN MUR CENTRIFUGAL OIL CLEANER DI PLTD MERAWANG - Rosa, Firlya; Rodiawan, Rodiawan (Mesin, 2016)
Centrifugal Oil Cleaner (COC) is a device that works using the principle of a rotating sedimentation. COC puts the object in the fix axis rotation by using the centrifugal force on gravity. COC is one of part in Diesel ALLAN 2 at PLTD Merawang. In the mantenace, parts of the rotor bodyat the COC should be cleaned by turn down the rotor nut cover of the rotor body. To simplify the process of opening a COC, it needs to be designed fixture to assist in turn down the nut so it will more efficient in time, minimize the equipment compared to manually process. The fixture is designed using Pahl-Beitz method and the manufacturing is processed using machine that is available on workshop. Manually process produces is faster 2 second than using the fixture. However, the fixture reduces using of equipment and involves only one operator so that operator safety is guaranteed.Key Word : COC, centrifugal, Fixture